Small scale temporal variability in the phytoplankton of Independencia Bay, Pisco, Perú - Ochoa, Noemí (2003)
Temporal variations at small scale of the coastal marine phytoplankton assemblages were studied. Water samples were collected at a fixed station in Bahia Independencia (Pisco-Peru). The sampling took place in the morning (08:00 h.) and afternoon (15:00 h) over a period of 29 days (March 28 to April 25, 1988). Surface temperatures also were taken, fluctuating from 15,4 °C to 17,2 °C. Diatoms were the principal component of the phytoplankton community and were more related with the total of phytoplankton. Other groups as Dinoflagellates, Coccolitophorids, Silicoflagellates and small flagellates were present but were less important. Skeletonema costatum was the dominant specie during the first nine days of sampling, after that it was substituted by Thalassionema nitzschioides, which remained as dominant until the end of the study. Small variation in species composition but large fluctuations in density of phytoplankton were recorded over a period of few hours. Small increments in temperature influenced in the phytoplankton assemblages.